Modification of natural petroleum adsorbent Sphagnum Dill; Petroleum and Coal; Vol. 58, iss. 5 - Rotar O. V. Olga Vasilievna; Rotar V. G. Viktor Grigoryevich; Gess T. Tatjyana; Iskrizhitsky A. A. Alexander Aleksandrovich; Vorobiev D. S. Daniel Sergeevich (2016, 2016)
Title screen